Enhancement of Mesopelagic Sinking Particle Fluxes Due to Upwelling, Aerosol Deposition, and Monsoonal Influences in the Northwestern South China Sea. Issue 1 (3rd January 2019) - Zhang, Jingjing; Li, Hongliang; Xuan, Jiliang; Wu, Zezhou; Yang, Zhi; Wiesner, Martin G.; Chen, Jianfang
Abstract: Time series data from a sediment trap at approximately 1, 000‐m depth in the northwestern South China Sea, July 2012 to April 2013, were used in combination with remote sensing and shipboard physical and biogeochemical data to quantify the effects of multiscale physical processes on sinking particle fluxes and the function of the local biological carbon pump. Total mass flux and the fluxes of its primary components—particulate organic carbon, calcium carbonate, opal, and lithogenic matter—exhibited similar temporal trends, with three conspicuous high‐flux events. These events occurred in the summer, autumn, and winter, attributable to upwelling, aerosol deposition, and the northeast monsoon, respectively. Together, these events accounted for only 40% of the total time but approximately 80% of the 10‐month total mass flux (21% during the upwelling event, 23% during the aerosol event, and 36% during the northeast monsoon event). Each event contributed its own unique biogeochemical overprint. For example, Calcareous phytoplankton benefited from both the upwelling and aerosol deposition events, but siliceous phytoplankton benefited more than calcifiers during the upwelling conditions. The biogenic sinking particles were primarily marine authigenic, while the lithogenic matter was mainly resuspended sediment from the neighboring slope. The high flux of lithogenic matter was due to scavenging by sinking organic matter and the ballasting effect, especially during the high‐flux periods. This study illustrates that episodic intraseasonal physical processes are as important as the most common major seasonal event—the northeast monsoon—in modulating the strength of the South China Sea biological carbon pump. Plain Language Summary: Sinking particles are the most important carriers of matter and energy within the marine biological carbon pump, which largely determines the ocean's capacity to sequester atmospheric carbon dioxide (CO2 ) over century timescales. Multiscale physical processes are important in modulating the strength and efficiency of the biological carbon pump, but the mechanisms and contributions of different physical forcings on mesopelagic sinking particle fluxes in the South China Sea (SCS) are still poorly known. Based on time series data from a sediment trap at approximately 1, 000‐m depth as well as upper layer physical and biogeochemical data, we have found that three discrete high‐flux events in the northwestern SCS were driven by upwelling, aerosol deposition and the northeast monsoon. Together, the three events accounted for nearly 80% of the total mass flux and nearly 75% of the total particulate organic carbon flux. Each event contributed nearly equal to the total particulate organic carbon flux, but each also contributed its own unique biogeochemical overprint. Our findings confirm the importance of multiscale physical processes on SCS biogeochemistry and in particular highlight the roles of upwelling and aerosol deposition, which are as important as the northeast monsoon in modulating the strength of the SCS biological carbon pump. Key Points: Trapped sinking particles were 36% biogenic (primarily marine authigenic) and 64% lithogenic (mainly neighboring resuspended sediment) Three discrete events driven by upwelling, aerosol deposition, and the northeast monsoon contributed nearly 80% of the total particles Intraseasonal events were as important as the seasonal monsoon in modulating the strength of the local biological carbon pump